Coming of Age in Segregated America: Critical Perspective on “Betsey Brown” by Ntozake Shange - Enamala Kalavathi,; Dr. E.S. Sharmila Sigamany, (The Bioscan, 2024)
Betsey Brown is a 1985 novel by Ntozake Shange. The novel is about the coming of age of one Betsey Brown, an upper-middle-class African American girl in the late 1950's, who is part of the first generation to experience desegregation. The novel takes place in St. Louis, MO. It deals with issues of family dynamics, community dynamics (especially in regard to race), and Betsey's developing sexuality. The Brown family is comprised of Betsey; her parents Greer and Jane; grandmother Vida; her three siblings, Margot, Sharon, and Allard; and her cousin Charlie. They live in an old Victorian home in St. Louis. As the book opens, the family is getting ready for a new day; Betsey is memorizing a poem by Paul Laurence Dunbar, in preparation for a school elocution contest. As the children head off to their school, which is all black, Vida notes how comfortable it is that they live in their own, isolated world-and expresses concern over the approach of desegregation. When Betsey gets to school, she hears two girls talking about her crush, Eugene Boyd. Despite the butterflies stirring in her stomach, she takes part in and wins her school's elocution competition. After school, she and some of her schoolmates go to the house of a friend of hers. Her friend is white, but poor. The girl's racist mother doesn't approve of her daughter having black friends, and her behavior causes one of the girls to leave. This prompts Betsey to think about racial integration, and particularly about the situation in Little Rock, Arkansas.